Frequency and Duration of Fecal Shedding of Salmonella Enteritidis by Experimentally Infected Laying Hens Housed in Enriched Colony Cages at Different Stocking Densities - Gast, Richard K.; Guraya, Rupa; Jones, Deana R.; Anderson, Kenneth E.; Karcher, Darrin M. (Frontiers in Veterinary Science, 2017)
Human infections with Salmonella Enteritidis are often attributed to the consumption of contaminated eggs, so the prevalence of this pathogen in egg-laying poultry is an important public health risk factor. Numerous and complex environmental influences on Salmonella persistence and transmission are exerted by management practices and housing facilities used in commercial egg production. In recent years, the animal welfare implications of poultry housing systems have guided the development of alternatives to traditional cage-based housing, but their food safety consequences are not yet fully understood. The present study assessed the effects of different bird stocking densities on the frequency and duration of fecal shedding of S. Enteritidis in groups of experimentally infected laying hens housed in colony cages enriched with perching and nesting areas. In two trials, groups of laying hens were distributed at two stocking densities (648 and 973 sq cm/bird) into enriched colony cages and (along with a group housed in conventional cages at 648 sq cm/bird) orally inoculated with doses of 1.0 × 10e8 cfu of S. Enteritidis. At 10 weekly post-inoculation intervals, samples of voided feces were collected from beneath each cage and cultured to detect S. Enteritidis. Fecal shedding of S. Enteritidis was detected for up to 10 wk post-inoculation by hens housed in all three housing treatment groups. The overall frequency of positive fecal cultures was significantly (P < 0.05) greater from conventional cages than from enriched colony cages (at the lower stocking density) for the total of all sampling dates (45.0% vs. 33.3%) and also for samples collected at 4-9 wk post-infection. Likewise, the frequency of S. Enteritidis isolation from feces from conventional cages was significantly greater than from enriched colony cages (at the higher hen stocking density) for the sum of all samples (45.0% vs. 36.7%) and at 6 wk post-inoculation. However, no significant differences in S. Enteritidis recovery from feces were observed between samples taken from enriched colony cages at the higher and lower stocking densities. These results suggest that stocking density is not the only housing-associated influence on the susceptibility of hens to intestinal colonization by S. Enteritidis.